Patterns of federal democracy: tensions, friction, or balance between two government dimensions. Issue 1 (29th July 2015) - Benz, Arthur; Sonnicksen, Jared
Abstract : Democracy and federalism are commonly viewed as complementary components of a political system. Conversely, a long-standing discourse claims the incompatibility of inevitable intergovernmental coordination in federalism with democracy, the former being viewed as an impediment or disruption to democratic governing. However, neither are the two inherently compatible nor inevitably incongruous. Instead, research and practice of democratic federations show that their relationship is one of multiple tensions. These may generate conflicts and impasses, yet can equally prove to be productive. To delineate these tensions, but also how different federal systems deal with them, this article examines federalism and democracy as two discrete, but interdependent institutional dimensions. Building upon this framework, we depict variants of coupling between institutions of federalism and democracy-based on selected cases. We demonstrate that particular modes of multilevel governance and intergovernmental relations are essential for linking the logics of federalism and democracy in loosely coupled, flexible patterns. Moreover, federal democracies can effectively cope with these tensions by continuously balancing power established in the two institutional dimensions.